Managing Work Family Conflict and Work Stress through Job Satisfaction and Its Impact on Employee Performance - Riana Gede I (Institute of Research and Community Outreach - Petra Christian University, 2018)
Work satisfaction has an important role in reducing work stress and work family conflict. This research aims to analyze the influence of work family conflict and work stress on the work satisfaction and performance of employees. The sample in this research is 46 married female employees. The data analysis technique used is the Partial Least Square (PLS) by using WarpPLS. The research results show that; work family conflict has a significant and negative influence on job satisfaction. Work family conflict has a significant and negative influence on employee performance. Work stress has a negative and significant influence on job satisfaction. Work stress has a negative and insignificant influence on employee performance. The analysis results provide information that work family conflict and work stress has an indirect influence on employee performance through job satisfaction. Furthermore, the indirect influence of work-family conflict on employee performance through job satisfaction is a full mediation. This means that job satisfaction has a strategic role in reducing the work stress and work family conflict so that it does not have a significant impact on employee performance. Job satisfaction can be improved by providing the feelings of fairness so that women can be satisfied with their job, conducting promotions, and supervisions. Finally, the social support of co-workers and management in the form of implementing family friendly policies is greatly needed to maintain the job satisfaction.